2015
DOI: 10.1093/jxb/erv462
|View full text |Cite
|
Sign up to set email alerts
|

Antisense down-regulation of the strawberry β-galactosidase geneFaβGal4increases cell wall galactose levels and reduces fruit softening

Abstract: HighlightWe identified a strawberry β-galactosidase gene involved in fruit ripening. Its silencing increases cell wall galactose levels and fruit firmness, suggesting galactose metabolism has a key role in strawberry softening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 54 publications
4
75
0
1
Order By: Relevance
“…The crude cell wall content of control and COS-treated fruits were 1.8% and 2.2%, respectively. The strawberry fruit softening has been characterized by the solubilization and depolymerization of pectins from cell walls [22]. According to previous report, the ionic pectin, its covalent bonding, hemicellulose, and cellulose content were closely related to the texture [21].…”
Section: Resultsmentioning
confidence: 99%
“…The crude cell wall content of control and COS-treated fruits were 1.8% and 2.2%, respectively. The strawberry fruit softening has been characterized by the solubilization and depolymerization of pectins from cell walls [22]. According to previous report, the ionic pectin, its covalent bonding, hemicellulose, and cellulose content were closely related to the texture [21].…”
Section: Resultsmentioning
confidence: 99%
“…RT-qPCR amplification was performed under the following conditions: 40 cycles at 95°C for 30 s and 58°C for 30 s. After amplification, the samples were maintained at 50°C for 1 min, and the temperature was gradually increased by 0.5°C every 10 s to perform the melting curve analysis. The interspacer 26S-18S strawberry RNA gene (housekeeping gene; Fv18S ) was used as an internal control to normalize the expression data (Raab et al, 2006; Hu et al, 2015; Medina-Puche et al, 2015; Paniagua et al, 2016; Wei et al, 2016). Three biological replicates with three technical replicates were assayed for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…PMEs catalyzed the de‐esterification of GalA from HG backbone, allowing calcium bridges formation and also providing the substrate of pectinases such as PGs and PLs . Besides the structure preservation of HGs, it has been shown that the side‐chain conformation of the RG‐I are tightly related to fruit firmness, being the study of β‐Gal and α‐Ara activities a matter of interest …”
Section: Discussionmentioning
confidence: 99%